Implementation of Documentation of Nursing Care in Wates Hospital - Erna Kurniawandari; Fatma Siti Fatimah (Alma Ata University Press, 2018)
The documentation of nursing care is the important part nurse duty, the best documentation of nursing care process that sees best and have a certain quality should be acurate, complete, and standard. Curently documenting of nursing care in Wates Hospital is practically not yet done according to Standard Operational Procedure. This study aims to know the description of the nursing care of documentation in Inpatient Room of Wates Hospital. This research is descriptive quantitatif which take the sample from inpatient documentation of nursing care in March 2017. The population was about 1106 documents of medical records which the sample obout 111 documents. The technique to take the sample was using cluster random. The research was held on June 2017. The data collection used medical record of patient. The univariat of data analysis used frequency distribution. This research showd that the completeness os documenting of nursing care in assessment aspect (77,5%), diagnosis (93,7%), planning (73,9%), action (45,9%), evaluation (76,6%), nursing care note (45%). The completeness of documentation of nursing care in Inpatient Room of Wates Hospital Kulon Progo is claimed complete (27,9%). Keywords: Nursing documentation, nursing process